Awareness and Performance of Iranian Nurses with Regard to Health Economics: A Cross-Sectional Study - Heydari, Abbas (N Am J Med Sci, 2015)
BACKGROUND: Health costs have risen everywhere, worldwide, and nurses play a pivotal role in cost savings and in contributing to the financial stability of hospitals. AIM: This study evaluated the awareness and performance of Iranian nursing staff, with regard to health economics. MATERIALS AND METHODS: A total of 175 nurses who worked in three teaching hospitals in Mashhad (Iran) were selected for this descriptive cross-sectional study, and data were gathered via a 27-item questionnaire. Statistical analysis was performed using one-way analysis of variance, multiple regression analysis, and Pearson's correlation coefficient. RESULTS: A total of 78% (n = 39) of nurses did not have a good awareness of health economics. The overall mean score for economic awareness was 5.9 ± 2.1 (possible range, 0-16), and for economic performance was 26.6 ± 4 (possible range, 0-44). There was a significant relationship between the economic awareness and performance of nurses, and nurses in higher positions had a greater awareness of health economics. CONCLUSIONS: Considering the inadequacy of the health economics awareness and performance of nurses, it is essential that efforts are made to enhance their knowledge and behavior with regard to economic issues and cost saving in all the fields of nursing, through the use of continuing education courses and workshops.